The Melodrama of Possessive Agency - Lome, Ragnhild (The Nordic Journal of Aesthetics, 2022)
In the last decades, streams within posthumanism and new materialism, have turned their attention to the phenomenon of agency. And they have done so in ways which open the phenomenon for social and cultural historical investigations, relevant for cultural studies and literary studies alike. This article uses a concrete case—the melodramatic novel Koloss by Norwegian author Finn Alnæs—in order to speculate on how a literary form can be seen to co-evolve—or in this case, clash—with fluctuations in the cultural history of agency. In the 1960s—the heydays of cybernetics—a discrepancy can be observed, between the nourishment of individualism in politics and advertisement, and the distribution of individual agency in the new emerging technologies of cybernetics, which pushed agency as a question in the forefront of a series of novels, Koloss included. However, the novel’s discussion of agency was ignored by the critics, as well as in the scholarly literature to follow. In an effort to get closer to the co-development of ideas of agency and aesthetic form, the article asks why this has been the case. Did the melodramatic form of the novel stand in the way of its aesthetic reflection on agency? And could the novel and its reception therefore be seen as an example of the existence of complex feedback-loops, between ideas of agency in a given culture and aesthetic form?